Aspectos morfológicos do fígado de tartaruga-da-amazônia Podocnemis expansa (Schweigger, 1812) (Testudines, Podocnemididae) e Phrynops geoffroanus (Schwiegger, 1812) (Testudines, Chelidae) - Moura, Léa Resende (2009)
CHAPTER II: The liver of P. expansa was characterized morphohistologically. To this end, twenty livers from clinically healthy male and female Podocnemis expansa (giant Amazon river turtle), weighing from 2.0 to 4,5 Kg, supplied by the commercial breeder Fazenda Moenda da Serra, in Araguapaz, state of Goiás, Brazil, were analyzed macro- and microscopically. The coelomatic cavity was opened and the topography of the fresh organs was examined visually. After the histological preparation, the slides were stained with Hematoxylin and Eosin (HE), Periodic Acid-Schiff (PAS), Gomori Trichrome, Reticulin and Picrosirius. The liver of P. expansa is a voluminous organ with an approximately rectangular shape and brown coloration, varying from light to dark shades, and is divided into a right lobe, left lobe, and a central portion. The right lobe is the largest of the three portions. The gall bladder is located in a depression in the caudal portion of the right lobe, where the gall duct begins and empties into the duodenum. Histologically, the hepatocytes are arranged in the form of double cords surrounded by winding sinusoidal capillaries. In cross section, they resemble acini containing approximately two to five hepatocytes surrounding a probable central biliary canaliculus. The hepatocytes are polyhedral or pyramidal in shape, of uniform size, with a few central nuclei and others displaced peripherally, and the cytoplasm is little eosinophilic when analyzed by the HE staining technique. The parenchyma is supported by delicate reticular fibers surrounding hepatocytes and sinusoids. The parenchyma and perisinusoidal spaces contain large quantities of melanomacrophages, mainly close to the portal spaces. CHAPTER III: The objective was the morphological characterization of the liver of Phrynops geoffroanus, popularly known as the freshwater turtle (cágado-de-barbicha in Portuguese), using six specimens from the Uberabinha River in Uberlândia, state of Minas Gerais, Brazil. The analyses involved anatomical and histological methods, and the microscopic aspects were described after the histological preparation. Fragments of liver were fixed in 10% formalin and absolute alcohol, embedded in paraffin, sectioned into four μm thick slices, and stained with HE, PAS, Gomori Trichrome and Reticulin. The liver of P. geoffroanus is a large light brown organ speckled with black spots, which represent melanin deposits. It is divided into four lobes, called the right lateral, right medial, left lateral and left medial lobes. The hepatocytes in longitudinal section are similar to double cords surrounded by winding sinusoidal capillaries, polyhedral shaped, of varying sizes, with a vacuolized aspect and with peripherally displaced nuclei. The cytoplasm is little eosinophilic and highly reactive to PAS, suggesting abundant intracytoplasmatic glycogen. The hepatic parenchyma is supported by delicate reticular fibers surrounding hepatocytes and sinusoids. Large quantities of melanomacrophages are present in the parenchyma and perisinusoidal spaces, mainly close to the portal spaces.